Improved susceptibility‐weighted imaging for high contrast and resolution thalamic nuclei mapping at 7T. Issue 3 (12th February 2020) - Jorge, João; Gretsch, Frédéric; Najdenovska, Elena; Tuleasca, Constantin; Levivier, Marc; Maeder, Philippe; Gallichan, Daniel; Marques, José P.; Bach Cuadra, Meritxell
Abstract : Purpose: The thalamus is an important brain structure and neurosurgical target, but its constituting nuclei are challenging to image non‐invasively. Recently, susceptibility‐weighted imaging (SWI) at ultra‐high field has shown promising capabilities for thalamic nuclei mapping. In this work, several methodological improvements were explored to enhance SWI quality and contrast, and specifically its ability for thalamic imaging. Methods: High‐resolution SWI was performed at 7T in healthy participants, and the following techniques were applied: (a) monitoring and retrospective correction of head motion and B 0 perturbations using integrated MR navigators, (b) segmentation and removal of venous vessels on the SWI data using vessel enhancement filtering, and (c) contrast enhancement by tuning the parameters of the SWI phase‐magnitude combination. The resulting improvements were evaluated with quantitative metrics of image quality, and by comparison to anatomo‐histological thalamic atlases. Results: Even with sub‐millimeter motion and natural breathing, motion and field correction produced clear improvements in both magnitude and phase data quality (76% and 41%, respectively). The improvements were stronger in cases of larger motion/field deviations, mitigating the dependence of image quality on subject performance. Optimizing the SWI phase‐magnitude combination yielded substantial improvements in image contrast, particularly in the thalamus, well beyond previously reported SWI results. The atlas comparisons provided compelling evidence of anatomical correspondence between SWI features and several thalamic nuclei, for example, the ventral intermediate nucleus. Vein detection performed favorably inside the thalamus, and vein removal further improved visualization. Conclusion: Altogether, the proposed developments substantially improve high‐resolution SWI, particularly for thalamic nuclei imaging.